2010
DOI: 10.1016/j.virol.2010.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma and vaccinia viruses exploit different mechanisms to enter and infect human cancer cells

Abstract: Myxoma (MYXV) and vaccinia virus (VACV) have recently emerged as potential oncolytic agents that can infect and kill different human cancer cells. Although both are structurally similar, it is unknown whether the pathway(s) used by these poxviruses to enter and cause oncolysis in cancer cells are mechanistically similar. Here, we compared the entry of MYXV and VACV-WR into various human cancer cells and observed significant differences: 1- Low pH treatment accelerates fusion-mediated entry of VACV but not MYXV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 60 publications
4
16
0
Order By: Relevance
“…Despite their similarities as members of the poxvirus family, the two viruses exhibit very divergent host tropisms, and they can differ dramatically in terms of which specific human cancer cells are permissive for infection and oncolysis (32). Although most poxviruses bind to a wide spectrum of mammalian cells in culture (15), there is growing evidence that the initial binding/entry step can be quite different among poxviruses (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their similarities as members of the poxvirus family, the two viruses exhibit very divergent host tropisms, and they can differ dramatically in terms of which specific human cancer cells are permissive for infection and oncolysis (32). Although most poxviruses bind to a wide spectrum of mammalian cells in culture (15), there is growing evidence that the initial binding/entry step can be quite different among poxviruses (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, the tropism of these two poxviruses can be quite different for many human cancer cells (32), and detailed studies comparing the attachment of MYXV and VACV virions to target cells have not yet been conducted. To directly test the binding of MYXV and VACV to different cell types and under different conditions, we have constructed fluorescently tagged versions of MYXV and VACV and then compared the binding and infection of these viruses to various human normal and cancerous cells.…”
mentioning
confidence: 99%
“…[8][9][10] MYXV is a viral oncolytic agent that is nonpathogenic to humans and mice but has natural tropism for a variety of human cancers. [11][12][13] In the course of developing MYXV as an ex vivo purging agent for transplant, we serendipitously discovered that NSG mice receiving human HCT xenografts treated ex vivo with MYXV developed no GVHD, lived longer, and yet still exhibited robust human hematopoietic engraftment in the recipient bone marrow. 14 We hypothesized that MYXV impaired the GVHD capacity of alloreactive donor T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that MYXV differs in some ways from VACV with regard to the mechanisms of cell entry. For example, MYXV entry is not stimulated by acid pH (57), an observation that may be related to the fact that MYXV does not encode an obvious homolog of the VACV A26 acidsensitive fusion suppressor protein. Of course, A26L is not the only VACV gene involved in promoting poxvirus entry and exit, which is missing from MYXV.…”
mentioning
confidence: 99%